Overview of Cancer and Medicinal Herbs used for Cancer Therapy - Chandra, Amrish (Asian Journal of Pharmaceutics (AJP), 2018)
Cancer is a disease in which abnormal cells proliferate in the body. It is a group of various diseases involving uncontrolled multiplication and division of abnormal cells in the body. These abnormal cells form malignant growths which called neoplasm. Nowadays, cancer considered as one of the most prevalent diseases in the world, and its mortality is increasing. It is necessary to investigate new strategies to prevent and treat disease. Herbal medicines block critical biochemical pathways converting normal cells to cancer cells for treatment. Herbal medicines block signal transduction in cancer which is a primary channel, by such as controlling nuclear factor-kB signaling pathway, protein tyrosine kinase pathway, and mitogen-activated protein kinases signal pathways. The various study reported that people with cancer commonly use herbal products because of no side effects on healthy cells. Herbal medicine is one of the most widely used alternative therapies by people with cancer. Clinically proven herbal remedies help to prevent or relieve the symptoms of cancer or treatment side effects by a conventional method. We have discussed various medicinal herbs found in India which have the potential to be used in cancer therapy. This present review will focus on the different medicinal plants containing chemical constituents used in the treatment of cancer with their possible mechanism of action.